Identification of Student Athlete Movement Activities during the Covid-19 Pandemic at Elementary School Level - Andhega Wijaya; Nanik Indahwati; Dwi Lorry Juniarisca; Eva Ferdita Yuhantin; Lutfhi Abdil Khuddus; Yusrina Salsabiila; Nartik Antika (Indonesian Journal of Primary Education, 2021)
Movement / physical activity is a very important matter for a child's life to support the performance of the movement itself, from the child as a student or the child becomes an athlete, when the child becomes an athlete, movements that already exist or have been studied must be monitored for stability and maximum of a movement that leads to skill. The purpose of the research is to describe and examine the movement activities of elementary school-level athletes throughout Surabaya during the COVID-19 pandemic. This type of quantitative descriptive research because in this study more emphasis on calculations of the data obtained through the google form. Discussions that occur in elementary schools in Surabaya are mostly non-athletes, there are about 87.2% who are students or ordinary students, and for athletes 12. 8% of the number of schools based on the division area between West, East, Central Surabaya. , north and south. This shows that it is quite good for the activities of the child who has this level of growth, amounting to 58.1%, this shows that these elementary school children are indeed good activities, above 50%. Movement activities by elementary school students can be said to be various movements, in general the exercises are aerobic and anaerobic, while the descriptions are jogging, running, cycling, sit-ups, push-ups, planks. With this existence, it is very much supported by various factors, including being supported by schools, teachers, parents, and open land in the area where they live so that the elementary students for movement or sports activities are well fulfilled. north and south. This shows that it is quite good for the activities of the child who has this level of growth, amounting to 58.1%, this shows that these elementary school children are indeed good activities, above 50%. Movement activities by elementary school students can be said to be various movements, in general the exercises are aerobic and anaerobic, while the descriptions are jogging, running, cycling, sit-ups, push-ups, planks. With this existence, it is very much supported by various factors, including being supported by schools, teachers, parents, and open land in the area where they live so that the elementary students for movement or sports activities are well fulfilled. north and south. This shows that it is quite good for the activities of the child who has this level of growth, amounting to 58.1%, this shows that these elementary school children are indeed good activities, above 50%. Movement activities by elementary school students can be said to be various movements, in general the exercises are aerobic and anaerobic, while the descriptions are jogging, running, cycling, sit-ups, push-ups, planks. With this existence, it is very much supported by various factors, including being supported by schools, teachers, parents, and open land in the area where they live so that the elementary students for movement or sports activities are well fulfilled. this shows that these elementary school children are indeed good activities, above 50%. Movement activities by elementary school students can be said to be various movements, in general the exercises are aerobic and anaerobic, while the descriptions are jogging, running, cycling, sit-ups, push-ups, planks. With this existence, it is very much supported by various factors, including being supported by schools, teachers, parents, and open land in the area where they live so that the elementary students for movement or sports activities are well fulfilled. this shows that these elementary school children are indeed good activities, above 50%. Movement activities by elementary school students can be said to be various movements, in general the exercises are aerobic and anaerobic, while the descriptions are jogging, running, cycling, sit-ups, push-ups, planks. With this existence, it is very much supported by various factors, including being supported by schools, teachers, parents, and open land in the area where they live so that the elementary students for movement or sports activities are well fulfilled